Pengaruh Karakteristik Komite Audit dan Pengungkapan Corporate Social Responsibility terhadap Financial Distress pada Perusahaan Sektor Basic Materials yang Terdaftar di Bursa Efek Indonesia Tahun 2020–2022 - Vania, Diva Clarissa (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2025)
This study aims to examine the effects of audit committee characteristics and Corporate Social Responsibility disclosure on financial distress in basic materials sector companies listed on the Indonesia Stock Exchange during the 2020–2022 period. Audit committee characteristics are represented by audit committee size, audit committee independence, audit committee meeting frequency, and audit committee competence. This research employs a quantitative associative approach using secondary data obtained from annual reports and financial statements. The sample was selected using purposive sampling and consisted of 45 companies from a population of 103 companies, resulting in 135 firm-year observations. Data were analyzed using panel data regression with EViews version 12. The results show that audit committee size has a negative and significant effect on financial distress, indicating that a larger audit committee may help reduce the likelihood of financial distress. Audit committee independence, audit committee meeting frequency, and audit committee competence do not have significant effects on financial distress. Meanwhile, Corporate Social Responsibility disclosure has a positive and significant effect on financial distress. The adjusted coefficient of determination is 8.05%, indicating that the independent variables explain a limited proportion of the variation in financial distress.